Doctors, chefs or hominin animals? Non-edible plants and Neanderthals. (15th September 2016) - Hardy, Karen; Buckley, Stephen; Huffman, Michael
Abstract : In 2013, Hardy et al. offered a broad behavioural context for the hypothesis that the ingestion of non-nutritional plants (yarrow and camomile) by Neanderthals was for the purpose of self-medication. Chemical traces of these plants had been detected in samples of dental calculus from Neanderthals at the site of El Sidrón, Spain, along with traces of bitumen and wood smoke, as well as starch granules that showed evidence of roasting (Hardy et al. 2012 ). Subsequently, the presence of traces of resin and a piece of non-edible conifer wood were also identified from these samples (Radini et al. 2016 ). Although not rejecting our interpretation for the presence of these two non-edible plants as evidence of medicinal plant use, two recent articles offer alternative scenarios for why and how those plants may have reached the mouth and, eventually, the dental calculus of the individual concerned. Buck and Stringer (2014 ) suggest that the plants were not deliberately ingested, and that the traces of yarrow and camomile were in fact embedded in the chyme, or stomach contents, of herbivore prey. Krief et al. (2015 ) propose two hypotheses: first, they suggest that the plants could have been used to flavour meat; second, while not ruling out the possibility that they could be medicinal, they argue on a technical point that the plants were not self-administered but were provided by a caregiver. Here, we examine these suggestions and consider their probability and feasibility as alternatives to our original proposal of self-medication.